Electron-positron plasma: kinetic symmetries and exact solutions - Taranov, V.B. (Вопросы атомной науки и техники, 2007)
Kinetic model for the high frequency electron-positron plasma waves is considered. Continuous symmetry transformations are found for the model by the indirect method, i.e. from the symmetries of the infinite set of equations for the moments of distribution functions. These symmetries, in combination with discrete ones, determine the form of the possible exact solutions, e.g. traveling waves and self similar local solutions determining the wave structure in the vicinity of its critical points. It is shown that the simplest form of extended symmetry is characteristic for this model. However, the extended symmetry is removed by the indirect moments method, since this symmetry is incompatible with the global conditions of the distribution functions non negativity and the existence of their moments. Розглянута кінетична модель високочастотних хвиль у електронно-позитронній плазмі. Неперервні перетворення симетрії цієї моделі одержані непрямим методом, а саме через симетрії нескінченної системи рівнянь для моментів функцій розподілу. Такі симетрії, в сукупності із дискретними, визначають форму можливих точних розв’язків, наприклад, біжучих хвиль і автомодельних локальних розв’язків, що визначають структуру хвиль поблизу їхніх критичних точок. Показано, що найпростіша форма розширеної симетрії є характерною для цієї моделі. Така розширена симетрія видаляється непрямим методом моментів, тому що вона є несумісною із глобальними умовами невід’ємності функцій розподілу і вимозі існування їхніх моментів. Рассмотрена кинетическая модель высокочастотных волн в электронно-позитронной плазме. Непрерывные преобразования симметрии этой модели найдены непрямым методом, т.е. получены из симметрий бесконечной системы уравнений для моментов функций распределения. Эти симметрии, в сочетании с симметриями дискретными, определяют форму возможных точных решений, например, бегущих волн и автомодельных локальных решений, описывающих структуру волн вблизи их критических точек. Показано, что простейшая форма расширенной симметрии характерна для этой модели. Эта расширенная симметрия удаляется непрямым методом моментов, так как она несовместима с глобальными условиями неотрицательности функций распределения и существования их моментов.